Pengaruh Financial Performance dan Sustainability Report terhadap Firm Value pada Perusahaan Sektor Energi dan Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024 - Yoan Eko Saputra; Fitrini Mansur; Muhammad Ridwan (Jurnal Riset Akuntansi, 2026)
This study aims to examine the effect of financial performance, proxied by Current Ratio (CR), Return on Assets (ROA), Debt to Assets Ratio (DAR), and Sustainability Report (SRDI) on firm value measured using Tobin’s Q in energy and industrial sector companies listed on the Indonesia Stock Exchange during 2022-2024. This research employs a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample was selected using a purposive sampling method, resulting in 40 companies observed over a three-year period. Data were analyzed using multiple linear regression. The findings indicate that CR, ROA, DAR, and SRDI simultaneously have a significant effect on firm value. Partially, Current Ratio has a positive effect on firm value, Return on Assets has a negative effect on firm value, Debt to Assets Ratio has no significant effect on firm value, while Sustainability Report Disclosure Index has a positive effect on firm value. These findings suggest that investors consider not only financial performance but also sustainability disclosure in evaluating corporate value.